The Perspective of Business Administration Students on Delivering Presentation - Amelia, Rini; Amelia, Rizky (Conference on English Language Teaching, 2023)
Oral presentation is one skill that must be mastered by the business administration students of the first and second semester of State Polytechnics of Banjarmasin when taking Bahasa Inggris 1and 2 subjects. Giving presentation is certainly not a simple thing to do especially for non-English department students. They must know the concept and put it well into practice. There have been a lot of previous research highlighting the importance of oral presentation skills and ways to develop them however little is exploring the way students view giving presentation itself. This is a descriptive qualitative study with interviews and questionnaires as the instruments to collect the data. The results showed that the students viewed delivering presentation positively but they still had many barriers in dealing with it. Nevertheless, they realize how importance it is for their future carrer. This study is significantly done since the findings could help the students to better deliver the presentation and assist the lecturers to help students to do so.